Tocopherol and tocotrienol contents of different varieties of rice in Malaysia. (25th June 2014) - Shammugasamy, Balakrishnan; Ramakrishnan, Yogeshini; Ghazali, Hasanah M; Muhammad, Kharidah
Abstract BACKGROUND The present study examined the contents of tocopherols and tocotrienols and their distribution in 58 different varieties of whole rice cultivated in Malaysia. The analytical method used was saponification of samples followed by dispersive liquid–liquid microextraction and reverse phase high‐performance liquid chromatography. RESULTS The total vitamin E contents of different varieties of whole rice ranged between 19.36 and 63.29 mg kg−1. Contents of vitamin E isomers varied among rice varieties both within and between grain color groups. Black‐pigmented rice showed significantly higher mean contents of α‐tocopherol, β‐tocopherol and α‐tocotrienol than non‐pigmented rice and red‐pigmented rice. Red‐pigmented rice had significantly lower mean contents of γ‐tocotrienol and total vitamin E than non‐pigmented rice. The mean contents of δ‐tocotrienol and total vitamin E in non‐pigmented rice, however, were similar to those in black‐pigmented rice. γ‐Tocotrienol was the predominant form of vitamin E isomer in all analyzed varieties. The Pearson correlations among vitamin E isomers and total vitamin E content of whole rice were also studied. CONCLUSION This study provides information on vitamin E content of different rice varieties that would be beneficial for decision making in genetic breeding of bioactive compound‐rich rice varieties. © 2014 Society of Chemical Industry